Multiphysics modelling of a hybrid magnetic bearing (HMB) for calculating power loss and temperature with different loss minimization strategies - Santra, Tapan; Roy, D; Choudhury, A B; Yamada, S (Tribologia - Finnish Journal of Tribology, 2019)
This paper represents a multiphysics modelling for calculating loss and temperature of a hybrid magnetic bearing (HMB) using finite element method (FEM). It also addresses the different loss minimization strategies for the HMB. The main sources of losses are identified as eddy current loss in permanent magnets, flywheel and copper loss in electromagnet. Due to these losses, the temperature distribution in different portions of HMB is computed using coupled field analysis. To minimize the eddy current loss, slits are fabricated in flywheel plate instead of a solid flywheel. The improvement of the control current is investigated by providing a coating of different metal, like copper, brass and stainless steel on the flywheel. A zero bias current (ZBC) scheme has been introduced where no bias current is required to levitate the rotor or to avoid singularity due to external disturbances, thus reducing the copper loss.